The plantpower way: Italia : delicious vegan recipes from the Italian countryside - Piatt, Julie; Roll, Rich (Avery, an imprint of Penguin Random House, 2018)
"A celebration of Italy and its delicious flavors, complete with 125 vegan recipes the whole family will love. Julie Piatt and Rich Roll have inspired countless people to embrace a plant-based lifestyle and lead healthier, more vibrant lives. Now they offer an irresistible guide to la bella vita with an inspiring collection of recipes that pay homage to Italy's rich food history. Filled with inventive and luscious recipes for Italy's time-honored dishes, [this book] reveals a fresh, beautiful, and healthful side to Italian cooking."--Page [4] of cover.